2016
DOI: 10.1002/lary.26262
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Evaluation of Micronized AlloDerm After Injection Laryngoplasty in a Rabbit Model

Abstract: NA Laryngoscope, 127:E166-E169, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…In previous work, we tested the efficacy of a MACD+ADSCs bioreagent for promoting VF medialization post RLN sectioning. We noted that compared to MACD alone, a medialization promoting volume three times larger was observed in the MACD+ADSC group at 12 weeks postinjection . Here, we focus on protein biomarkers of ADSC proliferation associated with the increased ellipsoid volume that correlate with the duration of clinical benefit.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In previous work, we tested the efficacy of a MACD+ADSCs bioreagent for promoting VF medialization post RLN sectioning. We noted that compared to MACD alone, a medialization promoting volume three times larger was observed in the MACD+ADSC group at 12 weeks postinjection . Here, we focus on protein biomarkers of ADSC proliferation associated with the increased ellipsoid volume that correlate with the duration of clinical benefit.…”
Section: Discussionmentioning
confidence: 97%
“…To distinguish exogenous from endogenous cells, injected stem cells have been labeled, but dyes and biologicals are rapidly extruded and the signal fades within days. We previously showed that a combination of micronized acellular dermis (MACD) and adipose mesenchymal stem cells (ADSCs) increased long‐term IML medialization volume . We hypothesized that continued in vivo proliferation of ADSCs was mostly responsible for these results, but inflammatory processes may have also played a part.…”
Section: Introductionmentioning
confidence: 99%
“…These revealed significant differences in volume retention between groups. For group 1, the mean volume at 4 weeks postlaryngoplasty was 341 ± 89 mm 3 , and at 12 weeks the mean volume was 62 ± 62 mm 3 , a difference of 81% in mean volumes ( P = .02) . In contrast, in the group that received undifferentiated ADSCs (group 2), there was no significant difference in volumes after 4 weeks compared to 12 weeks, with mean volumes of 295 ± 102 mm 3 and 235 ± 35 mm 3 , respectively ( P = .38).…”
Section: Resultsmentioning
confidence: 89%
“…The size of deposited material at each time point was estimated as previously described . Briefly, the volume of injection was approximated to an ellipse with the formula V = 4/3*π*( L /2* W /2* H /2), where L = length, W = width, and H = height.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation